New records of Solenocera barunajaya Crosnier, 1994 and Solenocera rathbuni Ramadan, 1938 (Crustacea: Decapoda: Penaeoidea) from the southwest coast of India - Purushothaman, P.; Chakraborty, Rekha Devi; Maheswarudu, G.; Kuberan, G. (Zootaxa, 2017)
The genus Solenocera Lucas, 1849 consist of 43 species, most with commercial importance and occurring in offshore, deeper waters (Pérez Farfante & Kensley 1997; De Grave & Fransen 2011). Twelve species in the genus Solenocera were reported from India, with a few contributing to the regular fishery (S. crassicornis, S. choprai, and S. hextii), and others seldom captured (S.alfonso, S.alticarinata, S.annectens, S.halli, S.koelbeli, S.melantho, S.pectinata, S.pectinulata and S.waltairensis). Members of the Solenoceridae are identified based on the key taxonomic characters of the genitalia and the cephalothorax. Major taxonomic references on solenocerids include Crosnier (1978, 1989), Perez Farfante (1977), and Dall (1999). Specimens are deposited in the Marine Biodiversity Museum at the Central Marine Fisheries Research Institute, Kerala (CMFRI).